Islamic Education in Indonesia and Malaysia (The Existence and Implementation until20th century) - Untung Margono (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2012)
This study discusses the comparison between the existence and the implementation of Islamic Education in Indonesia and Malaysia both from religious educational institutions and public educational institutions. The main problem focuses on: what are the issues that covered equality and differences based on the existence and implementation, and also what matters are dominantly and substantially considered as supporting factors for the cause of those two points (existence and implementation). The study describes the policy from the two countries toward Islamic Education including their goals and objectives. In addition, this study is also exploring the development of Islamic Education in the two countries based on the historical facts and current situation. Eventually, the analysis of comparison emphasized on the existing facts and reality.